Research on Optimization Strategies for Enhancing the Effectiveness of Judicial Advisory Systems - Zhao, Yule (Transactions on Social Science, Education and Humanities Research, 2024)
The planning and construction of Beijing’s urban sub-center is a significant strategic deployment made by the Central Committee of the Communist Party of China. Judicial suggestions serve as an important means for the people’s courts to extend their judicial functions and support the high-quality development of the sub-center. However, there is an urgent need to improve the level of participation in social governance. This article, through on-site research at the People’s Court of Tongzhou District, listening to special report meetings, and obtaining relevant sample data, aims to explore the feasibility of expanding the subject of judicial suggestions, balancing the types of judicial suggestion content, and addressing issues such as the low social consensus and insufficient foresight of the suggestions currently existing in the court system.